2017
DOI: 10.1002/mp.12178
|View full text |Cite
|
Sign up to set email alerts
|

Targeted dose enhancement in radiotherapy for breast cancer using gold nanoparticles, part 2: A treatment planning study

Abstract: The model provides a useful framework to estimate the nanoparticle-driven radiosensitivity in breast cancer treatment irradiation, accounting for the complex interplay between dose and GNP uptake distributions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…The main application could be their use in cancer diagnosis and therapies (Mesbahi and Carlo, 2010). In fact, it was demonstrated that GNPs contribute to enhance the generation of reactive oxygen species (ROS) such as ꞏOH, O 2and 1 O2, under irradiation of X-rays in the diagnostic range (Ferrero et al, 2017;Strigari et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The main application could be their use in cancer diagnosis and therapies (Mesbahi and Carlo, 2010). In fact, it was demonstrated that GNPs contribute to enhance the generation of reactive oxygen species (ROS) such as ꞏOH, O 2and 1 O2, under irradiation of X-rays in the diagnostic range (Ferrero et al, 2017;Strigari et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The model provides a useful framework to estimate the nanoparticle-driven radiosensitivity in treatment irradiations and could be applied to clinical treatment plan simulations as reported in the second part of the paper. 22…”
Section: Discussionmentioning
confidence: 99%
“…Higher biological effects resulted at kV energies, which is in accordance with the higher gold cross-section, and are lower for 6 and 15 MV irradiations, which were used in the treatment simulations in the second part of this work. 22 The RBE produced by any concentration of GNPs can be evaluated according to the analytical formulation by Eqs. (15) and (17).…”
Section: B Rbe Evaluationmentioning
confidence: 99%
See 2 more Smart Citations